(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2021)
The diachronic impact of Medieval political thought on the early Protestant politological views with particular reference to the subjects’ right to resist tyrannical rulers In his work Structural Anthropology (1963) Claude Lèvi Strauss distinguishes between synchronic and diachronic methodologies for studying societal phenomena and social entities. Synchronic methodologies focus on the contemporary position of social entities. In contradistinction to synchronic methodologies, diachronic approaches also consider the historical development of social phenomena. The complex nature of societies can often only be described in terms of atavistic tendencies. This is particularly true of early Reformational social institutions and their reliance on Medieval social and political structures. Because of the complexities of Medieval political culture in particular, political institutions and views cannot be described in terms of linear historical development. The resurgence of Roman law, Aristotelian philosophy and the reliance on ancient political institutions of Sparta and Athens, are only a few of the aspects reflecting the diachronic nature of Medieval political and constitutional institutions. In many instances, Medieval political authors relied on ideas from ancient political sources. The diachronic transmission of these Medieval political ideas in early Reformational political thought, produced a complex configuration of political positions on sovereignty, the rule of law, political freedom and resistance theory and differing in varying proportions from the classical Medieval views on these issues. In this article, the author investigates the diachronic Medieval origin of early Reformational political concepts and their impact on the formulation of political views pertaining to resistance to tyranny in particular.